Specyfika definiowania „przesłanek ograniczania” działalności gospodarczej na przykładzie zakazu reklamy aptek i punktów aptecznych - Jabłoński, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The fundamental issue raised in this elaboration is the “mechanism” for defining the conditions included by the legislator which led to the introduction of a ban on advertising pharmacies and pharmacy outlets in terms of the currently applicable content of article 94a(1) of the Pharmaceutical Law.
Keywords: advertising; prohibition of advertising pharmacies and pharmacy outlets; pharmaceutical law; restriction of individual freedoms and rights; constitution; freedoms and constitutional rights